Effect of Product Quality, Price, and Promotion to Purchase Decision - Lita Limpo; Abdul Rahim; H Hamzah (International Journal on Advanced Science, Education, and Religion, 2018)
This study aims to analyze the influence of product quality, price, and promotion of purchasing decision in Indonesia. The data used taken from some Indonesian people who usually drink local tea. The purposive sampling method used in the selection of respondents involving ninety-two people. The results of this study partially indicate that quality had a significant and positive effect on purchasing decisions by sixty percent. Price had a significant and positive effect on purchasing by forty-two percent. The promotion had a significant and positive effect on purchasing decisions by fifty percent. Simultaneously, the quality, price, and promotion significantly affected the purchase decision by seventy-two percent